Application of Topical Phosphodiesterase 4 Inhibitors in Mild to Moderate Atopic Dermatitis - Maria Elsa, Maria Elsa; Marsela, Marsela (International Medical Journal Corp. Ltd, 2024)
Background: The application of topical phosphodiesterase 4 (PDE4) inhibitors in the treatment of mild to moderate atopic dermatitis (AD) has emerged as a significant area of interest in dermatological research. The literature presents a comprehensive overview of the efficacy, safety, and therapeutic potential of these agents, particularly focusing on crisaborole and difamilast, which have shown promise in clinical settings. Literature Review: The foundational work by (Li et al., 2018) highlighted the efficacy and safety of crisaborole, establishing it as a viable non-steroidal treatment option for AD. This pivotal study demonstrated the ability of crisaborole to reduce inflammation by inhibiting pro-inflammatory cytokines, a mechanism that is crucial given the chronic nature of AD and the need for effective long-term management strategies. The safety profile of crisaborole, particularly its tolerability in pediatric populations, supports its role as a preferred alternative to traditional corticosteroids, which often come with significant side effects. Further expanding the therapeutic landscape, (Sharma et al., 2018) introduced East Indian sandalwood oil as a PDE4 inhibitor, suggesting its potential as a natural treatment option for inflammatory skin diseases, including AD. This exploration of alternative therapies enriches the available treatment modalities, particularly for patients seeking non-pharmacological interventions. Conclusion: In conclusion, the literature collectively supports the therapeutic potential of topical PDE4 inhibitors in managing mild to moderate atopic dermatitis. The studies reviewed emphasize their efficacy in reducing inflammation and pruritus while maintaining a favorable safety profile, thus presenting a promising alternative to conventional treatments. However, ongoing research is essential to fully understand the long-term effects and optimize treatment strategies for diverse patient populations.